2013
DOI: 10.1172/jci66113
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of imprinted genes inactivated by acquired chromosome 20q deletions

Abstract: Large regions of recurrent genomic loss are common in cancers; however, with a few well-characterized exceptions, how they contribute to tumor pathogenesis remains largely obscure. Here we identified primaterestricted imprinting of a gene cluster on chromosome 20 in the region commonly deleted in chronic myeloid malignancies. We showed that a single heterozygous 20q deletion consistently resulted in the complete loss of expression of the imprinted genes L3MBTL1 and SGK2, indicative of a pathogenetic role for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 68 publications
6
41
0
Order By: Relevance
“…Our macaque data show conserved L3MBTL1 imprinting between primate species and also expand the present understanding of tissue-specific imprinting at this locus, which is not imprinted in mouse or marsupial (Aziz et al 2013).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Our macaque data show conserved L3MBTL1 imprinting between primate species and also expand the present understanding of tissue-specific imprinting at this locus, which is not imprinted in mouse or marsupial (Aziz et al 2013).…”
Section: Discussionsupporting
confidence: 67%
“…Previously, we determined that the primate-specific imprinted gene, L3MBTL1, associates with a maternal germline imprint (Aziz et al 2013). In this study, all eight DMRs showed germline methylation consistent with the expected parental origin of the locus (Fig.…”
Section: Determination Of Germline Imprinting In the Primatesupporting
confidence: 66%
See 1 more Smart Citation
“…Genes included in the del(20q), such as L3MBTL1, have been studied for their possible involvement in leukemogenesis. However, sequencing analyses of 20q genes did not detect any mutation, 43 suggesting that haploinsufficiency of several genes of this chromosomal region could contribute to leukemogenesis. We compared the two minimal CDRs we identified with other studies (Online Supplementary Figure S6).…”
Section: Disease Progression and Prognosis In Myelofibrosismentioning
confidence: 94%
“…[10][11][12][13] It is hypothesized that haploinsufficiency of one or more tumor suppressors in a cluster of imprinted genes in the MDR could lead to a loss of expression, which may contribute to myeloid disorder development. [14][15][16] Mapping studies have focused on two such candidate tumor suppressors: L3MBTL1 and SGK2. Repression of L3MBTL1 has been shown to increase MYC expression in cell lines and could cooperate with SGK2, a regulator of the SWItch/sucrose nonfermentable-like chromatin-remodeling complex, in the epigenetic regulation of MYC expression.…”
Section: Introductionmentioning
confidence: 99%